LARVICIDAL ACTIVITY OF HEXANE-EXTRACTS OF Cinnamomum cassia and Zingiber officinale AND THEIR COMBINATION AGAINST Culex pipiens (DIPTERA: CULICIDAE) (Applied Biological Research, 2023)
Botanical products are encouraged for mosquito control because of their  low cost, rapid degradation, and low toxicity. The hexane extracts of  Cinnamomum cassia (C) and Zingiber officinale (Z) were assessed alone or  in combination on the 3rd instar of Culex pipiens. The LC50 values of C.  cassia and Z. officinale against Cx. pipiens were 317.61 and 269.4 µg mL-1,  respectively. The Z75%: C25% ratio was the most promising among the  different combinationtested, with IC50 value of 251.76 µg mL-1. The  histological sections of extract-treated larvae (C25%: Z75%) induced  degeneration of epithelial cells, degradation of microvilli, and loss of  nuclei. Antioxidant activity and phenolic content of Z. officinale hexane  extract showed a linear relationship. Z. officinale extract at 60.5 µg mL-1 possessed the highest hemolytic activity (73.9 ± 0.5%). Our results revealed  that the combined hexane extracts of C. cassia and Z. officinale provided  promising larvicidal action against Cx. pipiens.
Keywords: Cinnamomum cassia; Culex pipiens; combination effect; hemolysis; larvicide; Zingiber officinale